MEMBUKA PELUANG KEWIRAUSAHAAN TUNARUNGU MELALUI PEMBELAJARAN MENGGUNAKAN MODUL “TAPIS” - rusnaili rusnaili (Jurnal Guru Dikmen dan Diksus, 2021)
Education level in SMALB aims to prepare deaf students to challenges after graduating from school. One of the skills that deaf students is souvenir skills. In the SLB N Metro, the source book or special module for souvenir skills is not yet available. To make it easier for students to make souvenirs and understanding steps of the activities, they can use module. The purpose of this study was to determine the entrepreneurial abilities of deaf students of class XII SMALB, arranging a draft of the Tapis module, determine the results of module validation and responses to modules from students. The method in this research is descriptive research and development approach. The research stage is preliminary, development and testing. The research informants were three students and five validators. The data collection techniques used observation, interview and documentation. The research results obtained data from the entrepreneurial abilities of deaf students after using the module has increased of the score. The initial draft of the module consists of 4 chapters, after being validated the module is revised into 3 chapters and changes more interest title. The students' responses included easy to read modules, attractive pictures, make it easier to make souvenir brooches. The skilled “TAPIS” module for making innovative souvenirs was successfully developed using good validation results and the module user responses could understand the contents of the module.